2021
DOI: 10.1186/s12884-021-04183-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the invisible: perinatal health outcomes of unregistered women giving birth in Belgium, a population-based study

Abstract: Background The unregistered population remains under-researched because of its “invisible” status in statistics. Studies on perinatal health outcomes of unregistered women remains particularly limited. Our objectives were 1) to describe the sociodemographic profiles of women who are not legally residing in Belgium and 2) to analyze the associations of registration status with pregnancy outcomes according to socioeconomic status and nationality. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Due to their restriction from social assistance and legal employment, numerous studies have discovered that UMs’ lives are typically ruled by poverty and instability ( 25 ). These investigations also revealed that UMs did not have easy access to affordable accommodation and that there were few job opportunities available, most of which were on the black market, where wages were low and working conditions were poor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to their restriction from social assistance and legal employment, numerous studies have discovered that UMs’ lives are typically ruled by poverty and instability ( 25 ). These investigations also revealed that UMs did not have easy access to affordable accommodation and that there were few job opportunities available, most of which were on the black market, where wages were low and working conditions were poor.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study indicated that only undocumented migrants born in sub-Saharan Africa were at a significantly increased risk when considering both their location of birth and their legal status. Schoenborn, Spiegelaere, and Racape ( 25 ), found that the odds ratios for perinatal mortality in Belgium were statistically significantly higher for UMs compared to women with a nationality from Belgium who were captured on the National Population Register (NPR). The nationality groups of UMs with the strongest ORs were women from EU15 countries (OR (95% CI) 7.3 (6.0–8.95), p < 0.0001), followed by Belgium women without an NPR number (OR (95% CI) 4.3(3.3–5.4), p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brussels, three-quarters of births are to mothers with an immigrant background [21], and around 1.9% are to women who are not in the Belgian register (mostly undocumented) [22]. Different settings are available for the clinical follow-up of pregnancy, including hospitals, private practices, and community perinatal centres [23].…”
Section: Settingmentioning
confidence: 99%